Measuring Structural Vulnerability to Allocate Development Assistance and Adaptation Resources - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
Assessing the vulnerability which is independent of present policy is needed both to identif, the most vulnerable poor countries, and to design criteria for the allocation of international resources. With this regard two kinds of vulnerability and corresponding indices are considered: the structural economic vulnerability (as measured by the UN Economic Vulnerability Index, EVI) and the physical vulnerability to climate change (as measured by the Ferdi PVCCI Index); the former is more likely to be used for the allocation of development assistance, the latter for the allocation of adaptation resources. The two indices and their possible use are compared, while the rationale for their aggregation and for an integrated process of allocation is respectively discussed.Last update : January 2015
Keywords: F35; Q56; 330